2020
DOI: 10.1186/s12889-020-09365-2
|View full text |Cite
|
Sign up to set email alerts
|

Influences on NHS Health Check behaviours: a systematic review

Abstract: Background National Health Service Health Checks were introduced in 2009 to reduce cardiovascular disease (CVD) risks and events. Since then, national evaluations have highlighted the need to maximise the programme’s impact by improving coverage and outputs. To address these challenges it is important to understand the extent to which positive behaviours are influenced across the NHS Health Check pathway and encourage the promotion or minimisation of behavioural facilitators and barriers respectively. This stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 48 publications
(111 reference statements)
1
22
0
Order By: Relevance
“…In addition to these reviews (and their associated academic publications 9 19-21 ), a further three reviews relating to the NHS Health Check have been published to date, [22][23][24] and we have also identified two other systematic reviews focused on participation and patient experience in similar prevention programmes. 25 26 Drawing on the existing evidence, below we summarise what is currently known about the NHS Health Check programme: ► Coverage (proportion eligible who receive a Health Check) is known to vary substantially across regions and settings, but is consistently higher in older people, women and in more deprived populations, although this may reflect targeting.…”
Section: Open Accessmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to these reviews (and their associated academic publications 9 19-21 ), a further three reviews relating to the NHS Health Check have been published to date, [22][23][24] and we have also identified two other systematic reviews focused on participation and patient experience in similar prevention programmes. 25 26 Drawing on the existing evidence, below we summarise what is currently known about the NHS Health Check programme: ► Coverage (proportion eligible who receive a Health Check) is known to vary substantially across regions and settings, but is consistently higher in older people, women and in more deprived populations, although this may reflect targeting.…”
Section: Open Accessmentioning
confidence: 99%
“…Open access including the option to book an appointment during the call may overcome anticipated difficulties in making appointments and offer an opportunity to increase participants' understanding of the Health Check, 32 which may be barriers to uptake. 23 Other barriers may include aversion to preventive medicine, competing priorities and, for community pharmacy and outreach settings, concerns about privacy and confidentiality. 10 11 19 23 Some qualitative evidence highlights the convenience of these settings and the value of community ambassadors.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…The BCTTv1 has been used in systematic reviews on a range of health promotion interventions [20][21][22][23]. A recent study using the BCW, BCTTv1 and Theoretical Domain Framework suggested theoretical effective strategies to improve health check behaviour [24]. These suggested theoretical strategies can either implemented into an existing intervention or to inform future intervention design.…”
Section: The Behaviour Change Wheel (Bcw) Is a Framework That Guides Intervention Development Frommentioning
confidence: 99%